2016
DOI: 10.1149/2.0611614jes
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Properties of Lanthanum on the Liquid Gallium Electrode in LiCl-KCl Eutectic

Abstract: This work presents an electrochemical study of La(III) in the LiCl-KCl-LaCl 3 melt on a liquid gallium electrode. The reduction of the La(III) on a liquid gallium starts at −1.13 V (vs. Ag/AgCl) and is a one step process with three electrons transferred. The activities, activity coefficients and solubilities of La in La-Ga alloys were calculated by open circuit potential technique at the temperature range of 673 to 823 K. Moreover, galvanodynamic methods was also applied on a W electrode to evaluate the appare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…35 where i, i 0 , h have the similar meaning with eqn (8), A and E a present charge-transfer resistances (U), pre-exponential factor (A cm À2 ) and the reaction activation energy for Y(III)/Y(0) (kJ mol À1 ), respectively. Since there is a linear relationship between currents and over-potentials near the equilibrium potential, the chargetransfer resistances (R ct ) at different temperatures can be obtained by eqn (10).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…35 where i, i 0 , h have the similar meaning with eqn (8), A and E a present charge-transfer resistances (U), pre-exponential factor (A cm À2 ) and the reaction activation energy for Y(III)/Y(0) (kJ mol À1 ), respectively. Since there is a linear relationship between currents and over-potentials near the equilibrium potential, the chargetransfer resistances (R ct ) at different temperatures can be obtained by eqn (10).…”
Section: Resultsmentioning
confidence: 99%
“…For example, the electrode area is changeless, and the diffusion of deposited metal into the liquid metal is easier. 6,7 Thus, liquid Ga, [7][8][9][10][11] Bi, [12][13][14][15] Cd, 13,16 Zn, [17][18][19][20][21][22][23][24] Sn 25 were selected as cathode to separate REs from molten salts. The melting point of Pb metal is 600 K and boiling point is 1798 K, it is easy to melt but doesn't evaporate at 723-823 K. Thus, Pb metal seems to be a good candidate as the cathode material in separation and extraction of REs by molten salt electrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, a metal crucible is preferred due to its high strength. But, it is worth noting that the melting point of gallium is low under standard atmospheric pressure, and liquid gallium can be infiltrated into almost all metals to form alloys. , So, metallic crucibles cannot be used as IGZO containers. On the basis of the above analysis, a nonmetallic graphite crucible was selected as the cathode to collect the electrolytic product in this work due to its good electrical conductivity and low price.…”
Section: Introductionmentioning
confidence: 99%
“…14 Thus, liquid cathode is paid more attention because of its complete physical separation between the metal product and electrolyte, constant electrode area, and easy diffusion of deposited metal into liquid metal. Low melting metal and alloy, for example, Bi, [30][31][32] Sn, 33,34 Cd, 35,36 Pb, [37][38][39] Ga, 40,41 Zn 14,[42][43][44] metals and Al-Ga alloy [45][46][47] were explored as a liquid cathode. The feasibility of liquid metals (Sb, Bi, Pb, Sn, Ga) as cathode was systematically investigated in molten fluorides, Gibilaro et al found that the electroactivity domains and reactivity of liquid metals are Bi > Pb > Sn > Sb > Ga. 48 Lebedev 49 evaluated the separation factor between actinides and lanthanides on various cathodes in molten chlorides, and found that the separation order is Al > Ga > Pb > Zn > Bi > Sn > In > Cd > Tl.…”
mentioning
confidence: 99%